Studies on the Limestone Vegetation of Sahasradhara near Dehra Dun-phytosociological Studies: Importance Value Index - Malhotra, S. K. (Indian Forester, 1973)
The average relative frequency, relative density, relative dominance and the importance value of the dominant and co-dominant species in the different habitats of Sahasradbara area have been discussed.